Sedimentary facies of clastic-platform carbonate sediment strata of epicontinental sea in the Daniudi Gasfield, Ordos Basin - Guangquan Zhang; Lidong Mi (Natural Gas Industry B, 2021)
Mixed deposition is a sedimentary phenomenon of special significance to the tectonic movement, material supply, sea level change, and paleoclimate of the sedimentary environment. The sediments of the Late Carboniferous-Early Permian System in the North China Craton, which are composed of clastic rock and limestone, are mixed clastic-platform carbonate sediments in the epicontinental sea. Based on the geological and well logging data of nearly 100 exploratory wells and hundreds of development wells in the region, the lithologic association and cycle features of the Upper Carboniferous-Lower Permian were determined. From this data, the Benxi Formation and the Taiyuan Formation of the Daniudi Gasfield are considered to belong to a mixed clastic coastline-carbonate platform sedimentary system and coastal plain sedimentary system in the epicontinental sea. Based on the six transgressions and regressions during the Late Carboniferous-Early Permian epochs in the region, combined with the regional evolution history, this study analyzed the sedimentary evolution history of the Daniudi Gasfield from the Late Carboniferous to the Early Permian.